Análise espaço-temporal do risco à inundação na área urbana do município de Uruguaiana/RS - Aimon, Jonatas Giovani Silva (2017)
Over the years, man's use of nature has led to significant episodes of human and material loss, especially the last decade due to the advance of urbanization, which has been initiated by the search for better employment opportunities for the rural population. The municipality of Uruguaiana has its origin linked to the proximity of the Uruguay River, and trade with Argentina and Uruguay. As a result of this history, and the need for studies on natural hazards and planning, this study aims to analyze the spatial-temporal dynamics of flood risk in the urban area of the city of Uruguaiana / RS. Data from the municipal government, National Water Agency (ANA) were used as information base, applying the deductive method, combined with previous knowledge with knowledge based on other bibliographical references. For the construction of the Digital Terrain Model, the Arcgis 10.1® Top to Raster tool was used. The hazard, exposure to flood threat, was obtained by using the logarithmic function on the sets of observations extracted in the previous study of the maximum floods (above the 48 m altitude). Soon, their respective boundaries were obtained in the field for the classes 2/5/25/100 years (TR). Vulnerability, potential for losses and damages was mapped on the basis of field surveys, traversing the areas affected by the calculated TR, being evaluated the real estate of the urban area and the spatial distribution of the same, being after delimited small areas in the areas affected by the flood, Classified according to the Very High/High/Medium/Low Vulnerability classes. The detailing of the local topography revealed that the floods reaching the population are mainly due to the extrapolation of the water level in the Arroio Cacaréu and Arroio Salso de Cima. The mapping of the 245.63 ha, revealed a great differentiation within the same municipality, social segregation is clearly manifested in space. Most households with high (22.34%) or very high (8.40%) vulnerability, are concentrated near Arroio Cacaréu in the neighborhoods Francisca Tarrago and Cabo Luis Quevedo. After crossing the information plans were found 2,205 residences, with potential risk ranging from Low to Very High. Regarding the amount found, it is worth noting the need for attention to the households found in situations of High and Very High risk, totaling about 34.96% of the sample analyzed for study.